Pseudomonas oryzihabitans D1-104/3 and P. gessardii C31-106/3 differentially modulate the antioxidative response of duckweed (Lemna minor L.) to salt stress - Popržen, Tatjana; Antonić Reljin, Dragana; Uzelac, Branka; Milovančević, Marija; Paunović, Danijela; Trifunović-Momčilov, Milana; Marković, Marija; Raspor, Martin; Nikolić, Ivan; Stanković, Slaviša; Radulović, Olga (Frontiers in Microbiology, 2024)
IntroductionThe common duckweed (L. minor) is a model organism for investigation of plant physiology, especially stress-related responses. Its two physiological characteristics are of special interest: (1) salt-stressed duckweeds may accumulate starch, a precursor for biofuel; (2) duckweeds are associated with various beneficial (plant-growth promoting, PGP) bacterial strains. In this paper, we analyzed the role of two bacterial strains: Pseudomonas oryzihabitans D1-104/3 and P. gessardii C31-106/3 in regulation of duckweed's growth and antioxidative responses to salt (10 and 100 mM NaCl) and hypothesized that they alleviate salt-induced oxidative stress.MethodsFresh and dry weight, frond number, photosynthetic pigments, malondialdehyde (MDA) and hydrogen peroxide (H2O2), ascorbic acid (AsA), proline, total polyphenol (TPC) and starch content, as well as antioxidant capacity and antioxidant enzymatic activity were measured after 14 days. Fluorescence microscopy was used to visualize bacterial presence on duckweeds.ResultsFluorescence microscope revealed that Pseudomonas bacteria colonized all duckweed surfaces. The doubling time of duckweeds inoculated with P. gessardii C31-106/3 was significantly longer. Additionally, at 0 and 10 mM NaCl, this strain decreased chlorosis in duckweeds. Moreover, P. gessardii C31-106/3 increased dry-to-fresh-weight ratio, proline, chlorophyll a, b and carotenoid content at 100 mM, as well as AsA content in plants in NaCl-free medium, while P. oryzihabitans D1-104/3 increased AsA at 100 mM NaCl. Both bacterial strains decreased lipid peroxidation, while P. gessardii C31-106/3 increased and P. oryzihabitans D1-104/3 decreased H2O2 content at 100 mM and 0 mM NaCl, respectively. Bacteria significantly increased TPC and antioxidant capacity at 100 mM NaCl, particularly P. oryzihabitans D1-104/3. After 14 days, the SOD and POX activities were at the same level in all samples. At 100 mM NaCl, CAT activity was increased in all plants.DiscussionThe results of this study show that two Pseudomonas strains had markedly different effects on duckweed: while P. oryzihabitans D1-104/3 supported growth, P. gessardii C31-106/3 prioritized salt stress tolerance in duckweeds.